ANALISIS KEBUTUHAN MODEL PROBLEM-BASED LEARNING BERBANTUAN LKPD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN FISIKA - Hotmarlina Purba; Eka Ginting; Marnatauli Barasa; Eftika Purba; Mariati Simanjuntak (STKIP Subang, 2026)
Physics instruction at a private high school in Medan still focuses on lectures, which results in students being less active in class and their critical thinking skills needing improvement. Additionally, instructional models and media that engage students in problem-solving have not been successful. The conditions of physics instruction, students’ critical thinking skills, and the need to implement a problem-based learning (PBL) model supported by worksheets in physics instruction are the objectives of this study. This study was conducted using a qualitative descriptive method and a preliminary survey (pre-study). The research subjects consisted of 25 eleventh-grade students and one physics teacher. Data were collected through interviews and questionnaires. Qualitative descriptive analysis was performed on the interview data, and percentage analysis was performed on the questionnaire data. The results of the study indicate that students require more active and engaging learning that involves direct problem-solving; their interest in the use of learning media increased by 85% and fell into the high category, the problem-based learning model increased by 82% and fell into the high category, and their critical thinking skills increased by 78% and fell into the fairly high category. This study found that the implementation of a problem-based learning model supported by worksheets can help improve students’ learning activities and critical thinking skills in physics learning.